From the Old Financial to the New Commodity Economy in the Era of Stagflation - K. Molodyko (BRICS Law Journal)
In the process of reducing the speculative financial adjustment that artificially stimulates consumer demand in developed countries, the importance of suppliers of physical goods (commodities) from developing countries will increase. I don’t believe in a complete dictate of commodities producers because they are dependent on counter deliveries of technologies from developed countries. However, relationships will be built between holders of physical goods, and technologies will change significantly. The pricing function for commodities will be transferred to several exchanges of developing countries which will be controlled by the commodity producers. Food consumers from Asian and African developing countries will be provided with the BRICS assistance in the creation and protection of reserve food warehouses on their territory as well as supporting their key exports through the creation of a network of new commodity exchanges. The article substantiates the need for independent formation of regional prices by the BRICS countries for the primary goods of their exports on their exchanges. I propose various combinations among the founding countries for new commodity exchanges for mineral fertilizers, oil, diamonds, titanium, vanadium, palladium, wheat, and uranium. Trading on all these new commodity exchanges must take place entirely in the currencies of the engaged countries.